Early-Day Predicative Structures - Ebrahim Mohammad al Bab; Abdolhamid Saaleh Vaqaaf (دراسات في اللغة العربيّة وآدابها)
This article briefly explores the basic thoughts behind the predicative structure of sentences according to Sibawayh and his followers and also explores how this system developed and grew. As Sibawayhâs book is the first trustworthy source which has come down to us, the views in it are the points of departure for the study of syntax. This is also true about the predicative structure of sentences, which we find the most developed version in the contemporary works. The present research investigates the beginnings of this syntactic notion. The article can be divided into two parts: part one talks discusses predicative structures in nominative sentences part two deals with predicative structures in sentences with verbs. In both parts, there are statements from Sibawayh to show the structural relations in this linguistic form. Brief references are also made to later scholars in syntax when discussing the diachronic development of this structure.